Karakteristik Pemanfaatan Limbah Plastik dan Getah Damar sebagai Bahan Pengganti Aspal pada Perkerasan Lentur - Prihatini, Putri Rahmadilla; Nurdin, Ade; Sari, Dyah Kumala (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
Asphalt is one of the materials used as road pavement material. One way to prevent damage to road pavement due to vehicle load is to improve the quality and stability of the pavement, but considering that road pavement materials such as asphalt cannot be renewed, other alternative materials are needed as asphalt replacement materials. The material used as a substitute for asphalt is a mixture of plastic waste and resin resin. This utilization is intended to reduce the existence of more and more plastic waste and utilize materials from natural plants. This study aims to determine the characteristics of a mixture of plastic waste and resin resin as a substitute for asphalt on flexible pavement. The test results obtained with the addition of more plastic waste, the penetration test value decreases, the test value of the softening point increases, the specific gravity test value decreases.